SISTEM PENUNJANG KEPUTUSAN PUSAT KESEHATAN MASYARAKAT KUMUH PADAT KUMUH MISKIN BERDASARKAN DATA MINING MENGGUNAKAN DATA WAREHOUSE - Hendra Hendra; Astriana Mulyani (PETIR, 2015)
Designing and building a decision support system based on data mining using datawarehouse, especially health centersin the villages of Kampung Rawa in ranet system developmentin such a way to explore the added value in the form of information that had been unknown to themmanually from a database is a matter that will be discussed in this study. This research is a study ofcausal relationships of aset of variables to be studied. The method used in this study uses datamining techniques are then developed with the support ofthe data ware house with data retrievalfrom the health center's annual reportas a Decision Support System which can collect information inthe formulation of analytical techniques and decision-making procedures. The experiment wasconducted at the health centerin Central Jakarta Kampung Rawa. The first unit of analysis used inthis study are all part of heal this in Kampung Rawa Health Center. To obtain a representative unitof analysis, in this research, the classification by category Rukun Warga denseslums and poor slumcontainedin RW 01, RW 02, RW 06 and RW 08.